P33 Hypertension and murmur with a "normal echo" - an uncommon late presentation of coarctation of the aorta. (2nd March 2016) - Ramcharan, Tristan; Taylor, Andy; Chikermane, Ashish
Abstract : Background: Coarctation of the aorta accounts for 8–10% of all congenital heart disease, and generally tends to present in two peaks; newborn infants with congestive heart failure or older children with hypertension. 1, 2 We report an uncommon case of late presentation of coarctation of the aorta with an initial normal echocardiogram. History: A 15 year old girl was admitted to her DGH with episodes of dizziness and palpitations worsening over the previous 3 months. She was hypertensive above the 99th centile on admission with no blood pressure difference between upper and lower limbs. There was a grade 3/6 ejection systolic murmur noted with supra-sternal radiation; femoral pulses were palpable and the remaining systems examination was normal. Bloods tests were unremarkable and she had a normal ECG with no evidence of hypertrophy. Echocardiogram performed by the DGH adult cardiology team was reported as normal. However due to persisting hypertension and murmur she was referred to the paediatric cardiology tertiary centre for a drive-through review. At the tertiary centre she remained significantly hypertensive (systolic 152 mmHg), with a soft systolic murmur and weak femoral and pedal pulses noted. ECG was unremarkable and echocardiogram done showed good biventricular function with normal looking non-stenotic aortic valve with mild regurgitation and all other valves looked normal. The aortic arch was of normal calibre to the level of the left subclavian artery but the descending aorta could not be seen beyond this. An urgent MR Angiogram was therefore organised and this was done 3 weeks later which showed a small transverse aortic arch, hypoplastic isthmus and severe coarctation but with preserved LV Function and normal descending aorta. Her hypertension was gradually controlled using a combination of anti-hypertensives. She was subsequently discussed at the Joint Cardiac Conference with a plan for cardiac catherisation with stenting of the coarctation. This was done two months later with good flow across the stent. Peri-procedure CXR also showed typical pattern of rib notching secondary to collateral circulation. On subsequent clinic review she is doing well, with symptoms reduced, blood pressure controlled on antihypertensives and good cardiac function on follow-up echo. Conclusions: This case is interesting as in one aspect it describes the typical late presenting features of coarctation of the aorta, whilst at the same time highlighting the importance of a full cardiac assessment and not just reliance on echocardiography; its limitations in delineating extra-cardiac vascular anatomy exemplified. In paediatric cardiology practice, investigation should always include imaging of the aortic arch, which can be CT or MRI in an older child. Fortunately a good outcome, we could easily have failed this girl if the guidelines for investigating hypertension were not followed or the "normal" echocardiogram was taken as excluding coarctation of the aorta. References: Park's Pediatric Cardiology for Practitioners. 6 th Edition. Park M Rao, et al. Coarctation of the Aorta. Medscape. Available from URL: http://emedicine.medscape.com/article/895502-overview